APPLICATION OF CONTRAST BATH THERAPY AND 30-DEGREE FOOT ELEVATION TO REDUCE FOOT EDEMA IN PATIENTS WITH CONGESTIVE HEART FAILURE - Putri, Melsa; Idramsyah, Idramsyah; Husni, Husni (Universitas Airlangga, 2025)
Introduction: One of the most common cardiovascular diseases with a high morbidity and mortality rate is congestive heart failure (CHF). Patients with CHF often experience leg edema, which can cause discomfort and increase the risk of skin health issues. Therefore, nursing interventions are necessary to address the problem of leg edema in CHF patients. Methods: This study aims to provide a framework for the application of contrast bath therapy and 30-degree foot elevation procedures. This qualitative study employs a descriptive case study design with a therapeutic communication process approach, involving one participant with leg edema caused by CHF. Results: The implementation of the procedure begins with the pre-interaction phase, which involves assessing the patient's safety and protection needs and formulating a diagnosis regarding the risk of skin integrity damage. During the orientation phase, nurses provide therapeutic greetings, introductions, and obtain informed consent. In the interaction phase, the patient’s feet are soaked in warm water at 39°C for 3 minutes, followed by a soak in cold water at 16°C for 1 minute, then another soak in warm water at 39°C for 3 minutes. Afterward, the feet are dried with a towel, and the patient’s feet are positioned at a 30-degree elevation. The termination phase involves evaluating the patient's complaints and measuring the degree of edema. Conclusions: The contrast bath procedure and the 30-degree foot elevation, when combined with the therapeutic communication stages, can be effectively applied to treat edema in patients with congestive heart failure.